Reflection of oppression through imaginary homeland in Lakshmi persaud’s raise the lanterns high - Mani, Manimangai; Veeraputhran, Veeramohan (Centre for Resource, Research & Publication Services\, 2018)
The Caribbean is a place which is rich with diversified cultures. It is inhabited by people from various ethnic groups who were displaced during the era of European colonisation. One popular country from this region is Trinidad and Tobago whereby 42% of its population are ethnic Indians. The first Indians arrived in Trinidad as coolies to replace the vacancies created by the emancipated Black slaves. The focus of this research is on the Indians living on the island of Trinidad who managed to preserve their culture from their motherland, India which they left behind since their migration more than 250 years ago. The culture which treats women as second class citizens has been sustained on this island. This issue will be discussed by analysing evidences and incidences in Lakshmi Persaud’s novel titled Raise the Lanterns High (2004). Persaud is a Trinidadian Indian whose forefathers were Hindus from Uttar Pradesh who moved from India to the Caribbean in the 1890s. Persaud was born in 1939 in the small village of Streatham Lodge, Tunapuna, Trinidad. This paper will show how Persaud juxtaposes the culture practiced by the Trinidadian Indians which oppresses women just like back in the ancient India. Vasti, the protagonist is a liberal and smart woman who is set to an arranged marriage and she realises that the groom is the culprit in the rape incident she witnessed ten years ago. Persaud highlights these problems by creating an imaginary homeland which takes the readers some 300 years back. This paper will show how women in the ancient Kingdom of Jyotika were oppressed through the practice of suttee and how they succumbed to the cultural needs but at the same time tried to find solutions for these oppressions.